Supporting policy and institutional decision making towards agroecological transformations: Initial activities of the Agroecology Initiative - Frija, Aymen; Meinzen-Dick, Ruth S.; Place, Frank (CGIAR System Organization, 2022)
Agroecology calls for doing things differently. That includes not only farmers changing their agricultural practices but changing whole systems to support agroecological practices at the farm, community, regional, and even national level. Government set prices, taxes or subsidies for agricultural inputs and outputs can affect the incentives of farmers and other market agents to adopt agroecological practices. Institutions such as farmers’ organizations can help smallholders accessing the resources they need.